Rekonstruksi Evaluasi Pembelajaran Matematika Berbasis Problem Based Learning (Studi di Kelas X MA Bustanul 'Ulum Jayasakti Lampung Tengah) - Arini Ulfah Hidayati; Dedi Andrianto; Anggun Melani (Journal on Education, 2024)
Mathematics education in Indonesia faces challenges in improving student understanding and engagement, especially with complex topics like exponential equations. This study evaluates the effectiveness of Problem Based Learning (PBL) in teaching mathematics to 10th-grade students at MA Bustanul 'Ulum Jayasakti, Lampung Tengah. A quantitative experimental design was employed, involving two randomly selected classes: one using PBL and the other traditional methods. Results showed that students in the PBL class achieved an average score of 85, higher than the control class, which averaged 75. A t-test confirmed a significant difference with a p-value < 0.05. Additionally, 80% of students in the PBL class were more motivated to learn, compared to 60% in the control class. Observations revealed more active group discussions in the PBL class. The study concludes that PBL is more effective in improving student understanding, motivation, and participation than traditional methods.